(3OQGSI eJYebI aj GOGQI GdGYeGd GdOhdjIs - (3YHO GdQRGb(B, (3GdQMGMdIs; (3RGgO eMeO OjQj(B, s ((3YeGf(B:s (3ecJHI GdeLJeY GdYQHj(B,s, 2009)
(3eaGgje GdGOGQI GdeGdjI GdOhdjI h CSGSjGJgG h JWhQgG hfXQjI GdTQcI eJYOjI GdbhejI h fXQjGJ GdCSJKeGQ GdNGQLj GVGaI Gdi ejRGf GdeOahYGJ CSYGQ GdYedGJ h GOGQI GdCYeGd GdOhdjI GdYcSjI h HjFI GdGOGQI GdOhdjI eY feGPL hUjZ LOjOI ddefXeGJ Ydi GdeSJhi GdecGfj hGdHjFI GdKbGajI h eUGOQ GdJehjd GdeJGMI ddJehjd h Gdgjcd GdeGdj ddTQcI h eaghe JcdaI QGS GdeGd (B.s
(3eQGLY U(B.313s
Keywords: (3EOGQI GdGYeGds; (3GdEOGQI GdeGdjIs; (3GdYdGbGJ GdOhdjIs